Comparison of Wet and Dry Digestions in the Analysis of Fe in Spinach by Atomic Absorption Spectrophotometry - Irdhawati Irdhawati; I Gusti Ayu Putu Yunita Riyastini; Manuntun Manurung (The Journal of Pure and Applied Chemistry Research, 2022)
The method of digestion as a part of sample preparation is very important to determine the accuracy of the analysis result. In this study, the methods of wet and dry digestions were applied to determine of Fe content in several kinds of spinach obtained from the traditional market in Denpasar Bali. This research aimed to compare the result of Fe analysis by AAS method using both of digestion methods. This research was divided into several steps starting from sampling, determination of the samples species, sample preparation, digestion by wet digestion using aqua regia and dry digestion in the furnace, and Fe analysis by AAS. The result showed that the concentrations of Fe in root spinach, red spinach, cut spinach, and tricolor spinach through wet digestion method varied between 68.08–105.45 mg/kg, while the concentrations of Fe by dry digestion obtained between 27.52–42.03 mg/kg, which was over the accepted value. Based on the one-way ANOVA statistical test with a significance level of 5%, there was a significant differences of Fe concentration in spinaches by wet and dry digestions.